Analyzing predictors of customer satisfaction and assessment of retail banking problems in Pakistan - Muhammad Naeem Anjum; Bi Xiuchun; Jaffar Abbas; Zhang Shuguang (Cogent Business & Management, 2017)
The current study has tried to explore the types of services provided by Pakistan. A total of 1,089 bank customers affiliated with eight major banks across four major cities were interviewed through specified questionnaire. The gender wise distribution is 87% males and 13% female of the interviewed, individuals; while account type-based distribution is 24% business account, 37% salary account, and 39% general account holders. Regression analysis showed that customer satisfaction was governed by multiple significant predictors which include bank staff behavior (β = 0.18, p < 0.001), guidance inside bank (β = 0.04, p < 0.01), variety in service products (β = 0.03, p < 0.05), access to account statements (β = 0.11, p < 0.001), availability of cash (β = 0.11, p < 0.001) in ATM, and knowledge of bank staff (β = 0.40, p < 0.001). It is concluded that the retail banking in Pakistan has enormous room to capture more customers provided that private and public sector banks should invest more in infrastructure development along with the provision of swift banking services to their customers.
Keywords: 650